Bibliometric Evaluation of Moroccan Physicians of physical medicine and Rehabilitation Publications in PubMed: Evaluation of Moroccan Physicians of physical medicine and Rehabilitation Publications - Arabi, Hafid (Acta Biomedica Atenei Parmensis, 2021)
Backround: Moroccan Physicians in Physical Medicine and Rehabilitation (MP PMR) seek recognition at the international and national levels through publications. To our knowledge, no bibliometrics have been made to quantify these publications in indexed international journals. The aim is to quantify the publications MP PMR in indexed international journals.Methods and materiel: Is an observational study, we searched all the articles of the MP PMR published in the PubMed database until December 2019. The number of MP PMR articles was reported by academic academic centers, article type and indexed journal type.Results: We have found 26 articles since the creation of PMR in Morocco. The number of articles is correlated with the number of MP PMR remaining to 75 doctors and especially the ten professors. However, their contribution compared to their colleagues from other countries is promising. Scientific publications were limited to clinical cases in half of the cases. English was the dominant language of the works. Collaboration with foreign PMR was only with the French in 38.46% of cases. Only one French magazine took 34.61% of the works.Conclusion:  A lot of effort needs to be made by everyone, MP PMR and politicians to improve the quality and quantity of publications, research methodology and medical writing is one way, learning English in is another. Collaboration with other foreign collaborators is a necessity for a better visibility of publications.